Conditions of Halitosis in Patients with Tonsillitis - Dwi Ariani; Pindobilowo (Formosa Journal of Sustainable Research, 2023)
Tonsillitis (Tonsillitis) is a condition caused by trapped plaque which is formed from the accumulation of sulfur-producing bacteria, fungi, sloughed off cells, and food debris that sticks to the palatine tonsillar crypts. This plaque can cause bad breath (halitosis). Purpose: to determine the impact of patients with tonsillitis (tonsillitis) on halitosis. Methods: This literature study uses Narrative Review by analyzing various journals from the online database BMC Oral Health, PubMed, and Google Scholar which are related to Halitosis in Tonsillitis sufferers. Results: Within two weeks of Tonsillitis treatment, the halitosis was excavated and disappeared. Conclusion: Tonsillitis is one of the causes of bad breath. Actions applied are Tonsillitis removal, giving mouth rinses, antibiotics, and maintenance of oral hygiene